PANEL PELACAK SURYA SUMBU GANDA MODE OTOMATIS BERBASIS ARDUINO UNO SEBAGAI CATU DAYA MOTOR POMPA AIR - Eko Bayu; Sri Widoretno; Mukhlison Mukhlison (Jurnal Qua Teknika, 2022)
The energy source for electricity generation in Indonesia is mostly supplied from fossil energy, but this energy source will run out in the next 20 years. Various researches are now leading to the development of alternative energy sources such as solar energy. There are two kinds of solar energy utilization technologies, namely solar thermal energy technology and solar photovoltaic energy. Thermal solar energy in Indonesia is generally used for the drying process of agricultural and marine products, while photovoltaic solar energy is used to meet electricity needs, especially in remote areas. Most solar panels are installed permanently at a fixed angle. This causes the solar panels to be unable to absorb solar heat optimally because the sun is always moving. Therefore we need a tool that can move solar panels to follow the direction of the sunlight. The tool used is known as a solar tracker panel. This tool consists of an Arduino Uno as a microcontroller, an LDR (light dependent resistor) as a sensor and a servo motor to drive the solar panels. This tool is double axis, so it can (up and down) as well (to the left and right). The purpose of making this tool is to optimize the absorption of sunlight into the solar panels in order to further reduce the cost of spending electricity PLN. This type of research used in this research is quantitative research with a descriptive approach. The test results proved to be more efficient than the patented on-site solar panels. This tool is applied as a source of energy for water pumps and also for other items such as lamps,.etc